2018
DOI: 10.3389/fpls.2018.01327
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Biostimulant Mode of Action Using Novel Multi-Trait High-Throughput Screening of Arabidopsis Germination and Rosette Growth

Abstract: Environmental stresses have a significant effect on agricultural crop productivity worldwide. Exposure of seeds to abiotic stresses, such as salinity among others, results in lower seed viability, reduced germination, and poor seedling establishment. Alternative agronomic practices, e.g., the use of plant biostimulants, have attracted considerable interest from the scientific community and commercial enterprises. Biostimulants, i.e., products of biological origin (including bacteria, fungi, seaweeds, higher pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 41 publications
2
62
0
2
Order By: Relevance
“…These results suggest that the use of these microalgae extract as priming treatment, may be a good alternative to other priming methods adopted for sugar beet, according to Islam et al [ 28 ], who observed that the higher the seedling vigor index (SVI) value, the higher the positive effect on seed germination. Moreover, in accordance with Ugena et al [ 35 ], pre-sowing treatment with different biostimulant compounds, aiming to increase the vigor of seedlings, represents an innovative alternative to cope with different kinds of stresses. Comprehensively, all these results taken together suggest that best results, in terms of the germination process as well as root morphological traits, were reached by using the concentrations C2 and C3 of C. vulgaris extract, showing that this microalgal extract, besides exerting a biostimulant effect when added to the growth medium of sugar beet seedlings [ 19 ], may also be used as a priming method positively affecting the sugar beet seed germination.…”
Section: Resultsmentioning
confidence: 65%
“…These results suggest that the use of these microalgae extract as priming treatment, may be a good alternative to other priming methods adopted for sugar beet, according to Islam et al [ 28 ], who observed that the higher the seedling vigor index (SVI) value, the higher the positive effect on seed germination. Moreover, in accordance with Ugena et al [ 35 ], pre-sowing treatment with different biostimulant compounds, aiming to increase the vigor of seedlings, represents an innovative alternative to cope with different kinds of stresses. Comprehensively, all these results taken together suggest that best results, in terms of the germination process as well as root morphological traits, were reached by using the concentrations C2 and C3 of C. vulgaris extract, showing that this microalgal extract, besides exerting a biostimulant effect when added to the growth medium of sugar beet seedlings [ 19 ], may also be used as a priming method positively affecting the sugar beet seed germination.…”
Section: Resultsmentioning
confidence: 65%
“…Soil salinity is one of the largest constraints in agriculture, leading to a decrease in plant productivity and agriculture, resulting in approximately 20% of all yield loss [1,2,81]. There is a time constraint on this issue as the world population is growing extensively and a 50% increase in food production will be needed by as early as 2030 [82], while it is estimated that 50% of all arable soil will be salinized by 2050 [36]. However, unravelling these mechanisms and implementing the knowledge gained is a slow process and a large number of questions still remain unanswered [52], a common theme in plant research due to the complexity of the regulatory networks and crosstalk between signaling pathways and plant metabolism as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…Agricultural activity should ensure crop production plant's ability to intercept light. The use of high-throughput imaging analysis system allows to successfully integrate the experiments involving many variables, a large number of samples, and multiple comparisons [36]. Moreover, the high-throughput image analysis system is a non-invasive method that has the potential to determine the plant phenotypic response to experimental variable(s) (e.g., abiotic stress conditions), throughout the growing (or part of it) of experimental crops [24,25,37].…”
Section: Introductionmentioning
confidence: 99%
“…The application of such integrated approach could offer a better explanation of the mechanism(s) of action of different PBS molecules or compounds on crops. This can be obtained by the identification of several biomarkers of PBS action as reported in Paul et al (2019b) and Ugena et al (2018) [34,36].…”
Section: Introductionmentioning
confidence: 99%